The content of myosin heavy chains in hindlimb muscles of female and male rats - Drzymala-Celichowska, H; Karolczak, J; Redowicz, M J; Bukowska, D (Journal of physiology and pharmacology : an official journal of the Polish Physiological Society, 2012)
The aim of the study was to test whether the considerable differences in the hindlimb muscles mass, the number and diameter of muscles fibers were connected with differences in the myosin heavy chain isoform content (expressed as the percentage of the given isoform in respect to total myosin heavy chains). Therefore, the content of myosin heavy chain (MHC) isoforms was studied in four hindlimb muscles: flexor digitorum brevis, soleus, tibialis anterior and gastrocnemius medialis of female and male rats by means of polyacrylamide gel electrophoresis supplemented with densitometric analyses. Muscles were isolated and homogenized prior to electrophoretic analysis. The most interesting result concerned considerably different composition of myosin isoforms for male and female subjects in the slow soleus muscles, which contained predominantly slow MHC isoform (MHC I). However, in the male muscle about 13% of IIa isoform (MHC IIa) was also detected; this isoform was not found in the majority of the studied female muscles (81% of muscle samples). This dimorphic difference was further confirmed by immunofluorescence stainining for slow and fast skeletal myosin isoforms and by assessment of the fiber ATPase activity. For the three remaining fast muscles (flexor digitorum brevis, tibialis anterior and gastrocnemius medialis) all four MHC isoforms were detected with the fast isoforms being dominant ones. However, there were not statistically significant differences observed between males and females, with the exception of IIx isoform, which was more frequent in male tibialis anterior muscle.